Blepharochalasis: Possibly associated with matrix metalloproteinases. Issue 6 (10th May 2014) - Motegi, Sei‐ichiro; Uchiyama, Akihiko; Yamada, Kazuya; Ogino, Sachiko; Takeuchi, Yuko; Ishikawa, Osamu
Abstract Blepharochalasis is a rare disorder characterized by recurrent episodic swelling of eyelids, eventually leading to atrophy of skin. Although immunological mechanisms may be involved in the degradation of elastic fibers, the pathogenesis is not well characterized. We report a 10‐year‐old Japanese boy with an 11‐month history of the swelling of bilateral upper eyelids with atrophic skin. Attacks of non‐painful swelling in eyelids with erythema have recurred several times a month and lasted for 2–3 days. Histological examination revealed perivascular and interstitial infiltration of lymphocytes in the dermis. Elastica Van Gieson staining showed a marked decrease of elastic fibers throughout the dermis. Results of direct and indirect immunofluorescence analyses were negative. Staining of matrix metalloproteinase (MMP)‐3 and MMP‐9 was observed in and around infiltrating cells in the dermis, suggesting that MMP‐3 and MMP‐9 may play, in part, roles in the development of blepharochalasis, and that inhibitor of MMP may have a possibility of therapeutic application.